Local Government Internally Generated Revenue And Administrative Costs: A Question Of Efficiency. - AbdulKareem, Abdulrazaq Kayode; Abdulhakeem, Adejumo; Abdulrasaq Ajadi, Ishola (Journal of Techno-Social, 2018)
Internally generated revenue is one the sources of revenue open to the local governments. These revenues are generated within the confines of the local government mostly through services provided to the local population. This source of revenue required some efforts to carryout such as administrative expenses like consultancy fees and stationeries. In the past, little efforts have been geared towards investigating the efficiency of revenue collection and the cost involved, as efficiency is a major criterion in the revenue collection. Therefore, this paper dwells into the relationship between the internal source of local government revenue, and the costs involved in the generation of the revenue to measure the degree of efficiency in the revenue administration. The study used survey questionnaire administered to the revenue section of local governments in North Central Nigeria to seek their opinion on the research question of whether the administrative cost of revenue impacts on the rate of revenue generated. The study applied chi-square statistical method to analyse the result of the questionnaire. From the result, where the null hypothesis was rejected shows that there is a relationship between the rate of administrative cost and revenue generated. Therefore, the study concludes that it becomes necessary for the local government to become more efficient in their revenue generating capacity due to the dwindling nature of funds from the center.